2007
DOI: 10.1128/jvi.00601-07
|View full text |Cite|
|
Sign up to set email alerts
|

Vaccinia Virus Entry, Exit, and Interaction with Differentiated Human Airway Epithelia

Abstract: Variola virus, the causative agent of smallpox, enters and exits the host via the respiratory route. To better understand the pathogenesis of poxvirus infection and its interaction with respiratory epithelia, we used vaccinia virus and examined its interaction with primary cultures of well-differentiated human airway epithelia. We found that vaccinia virus preferentially infected the epithelia through the basolateral membrane and released viral progeny across the apical membrane. Despite infection and virus pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
3
10
0
Order By: Relevance
“…In contrast to what has been established previously for several respiratory viruses such as influenza virus, rhinovirus (RV), coronavirus, or respiratory syncytial virus (RSV) (Matrosovich et al, 2004;Johnson et al, 2015;Griggs et al, 2017), HPeVs infected airway epithelium more efficiently from the basolateral rather than the apical surface. Similarly, basolateral entry in the HAE cultures has been reported for vaccinia virus, reovirus, some adeno-and arenaviruses and measles virus (Sinn et al, 2002;Vermeer et al, 2007;Dylla et al, 2008;Excoffon et al, 2008;Lütschg et al, 2011). In line with our HPeV data, vaccinia, reo-, and measles viruses also exhibited apical shedding of the progeny virions (Sinn et al, 2002;Vermeer et al, 2007;Excoffon et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast to what has been established previously for several respiratory viruses such as influenza virus, rhinovirus (RV), coronavirus, or respiratory syncytial virus (RSV) (Matrosovich et al, 2004;Johnson et al, 2015;Griggs et al, 2017), HPeVs infected airway epithelium more efficiently from the basolateral rather than the apical surface. Similarly, basolateral entry in the HAE cultures has been reported for vaccinia virus, reovirus, some adeno-and arenaviruses and measles virus (Sinn et al, 2002;Vermeer et al, 2007;Dylla et al, 2008;Excoffon et al, 2008;Lütschg et al, 2011). In line with our HPeV data, vaccinia, reo-, and measles viruses also exhibited apical shedding of the progeny virions (Sinn et al, 2002;Vermeer et al, 2007;Excoffon et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, basolateral entry in the HAE cultures has been reported for vaccinia virus, reovirus, some adeno-and arenaviruses and measles virus (Sinn et al, 2002;Vermeer et al, 2007;Dylla et al, 2008;Excoffon et al, 2008;Lütschg et al, 2011). In line with our HPeV data, vaccinia, reo-, and measles viruses also exhibited apical shedding of the progeny virions (Sinn et al, 2002;Vermeer et al, 2007;Excoffon et al, 2008). We found that both HPeV1 and HPeV3 targeted the p63+ basal cells for replication.…”
Section: Discussionsupporting
confidence: 90%
“…VACV replication preferentially occurs in cutaneous sites with compromised barrier function ( 39 ), where there is increased access to the basolateral membrane ( 40 ). Viral entry begins with attachment of four viral proteins (A26, A27, D8 and H3) of the mature virion to cell surface glycosaminoglycans (GAGs), extracellular matrix proteins, and, at lipid rafts, integrin membrane receptors ( 41 , 42 ).…”
Section: Classical Skin-tropic Virusesmentioning
confidence: 99%
“…These results limited the use of ISD as dsDNA challenge stimulus in human airway epithelial cells for studying ABCF1 function. Vaccinia virus is a dsDNA virus that is able to infect airway epithelial cells (19)(20)(21)(22)(23). We therefore determined the response of human airway epithelial cells to VACV-70, a 70bp dsDNA oligonucleotide containing Vaccinia virus motifs (51).…”
Section: The Dsdna Viral Mimic Vacv-70 Induces Cxcl10 and An Antiviramentioning
confidence: 99%
“…Like RNA viruses, adenovirus is able to infect airway epithelium followed by replication, which leads to a variety of innate immune defences able to sense viral nucleic acids and proteins (14,17,18). Vaccinia virus is another dsDNA virus that is able to infect airway epithelium and has been explored for capacity to genetically engineer the virus for transgene delivery, vaccination strategies, and studying Variola virus infections (19)(20)(21)(22)(23). Exploring how the airway epithelium responds to viruses may provide new strategies for controlling infections, optimizing transgene delivery, and vaccination strategies relevant in lung health and disease.…”
Section: Introductionmentioning
confidence: 99%